Brief Report: Interleukin‐6 as an Inflammatory Mediator and Target of Therapy in Chronic Periaortitis. Issue 9 (26th August 2013) - Vaglio, Augusto; Catanoso, Maria G.; Spaggiari, Lucia; Magnani, Luca; Pipitone, Nicolò; Macchioni, Pierluigi; Pulsatelli, Lia; Nicastro, Maria; Becchi, Gabriella; Corradi, Domenico; Versari, Annibale; Boiardi, Luigi; et al.
<x xml:space="preserve">Abstract</x> Objective Chronic periaortitis (CP) usually responds to glucocorticoids, but some patients have glucocorticoid‐refractory disease or contraindications to glucocorticoid therapy. This study was undertaken to evaluate treatment with the anti–interleukin‐6 receptor (anti–IL‐6R) antibody tocilizumab in 2 patients with CP, one with refractory disease and the other with contraindications to glucocorticoids, and to assess IL‐6 levels in an additional cohort of patients with CP. Methods Both patients were given intravenous tocilizumab (8 mg/kg) once every 4 weeks for 6 months. Serum IL‐6 was measured in 22 patients with active CP and 16 healthy controls. Tissue IL‐6 expression was assessed by confocal microscopy in biopsy specimens obtained from 6 patients with CP. Results In the first patient, whose disease was refractory to various immunosuppressive treatments, tocilizumab added to ongoing therapy with prednisone and methotrexate allowed prednisone withdrawal and induced resolution of symptoms, acute‐phase reactant normalization, and reduction in 18F‐fluorodeoxyglucose (18F‐FDG) uptake on positron emission tomography. The patient experienced a relapse 7 months later and was successfully retreated with tocilizumab. In the second patient, who was unable to tolerate glucocorticoids because of psychiatric side effects, tocilizumab monotherapy induced sustained clinical and laboratory remission, 18F‐FDG uptake disappearance, and CP shrinkage. Serum IL‐6 levels were significantly higher in patients with active CP than in controls (P < 0.0001), and IL‐6 was abundantly expressed in biopsy specimens from CP patients, particularly by T cells, B cells, histiocytes, fibroblasts, and vascular smooth muscle cells. Conclusion Tocilizumab may be a therapeutic option for CP. The systemic and tissue up‐regulation of IL‐6 in CP, together with the clinical benefit of IL‐6R blockade observed in our 2 patients, suggest that IL‐6 may contribute to CP pathogenesis.